2007
DOI: 10.1021/jp074814e
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Reaction Mechanism of Li−Mg−Al−N−H System for Reversible Hydrogen Storage

Abstract: Complex metal hydrides are attracting much attention as a class of candidate materials for hydrogen storage. Lithium-based complex hydrides, including lithium aluminum hydrides (LiAlH4 and Li3AlH6), are among the most promising materials, owing to their high hydrogen contents. In the present work, we investigated the dehydrogenation/rehydrogenation reactions of a combined system of Li3AlH6 and Mg(NH2)2, which has a theoretical hydrogen capacity of 6.5 wt %. Thermogravimetric analysis of hydrogenated 2/3Al−Li2M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 43 publications
6
37
1
Order By: Relevance
“…In order to improve the thermodynamic properties of binary Li-N-H system, Li was compositionally substituted by other elements, and several types of ternary or multinary metal-N-H systems (e.g. Li-Mg-N-H [5][6][7][8][9], Li-Ca-N-H [10,11], Li-Al-N-H [12][13][14], Li-B-N-H [12,15], Li-Co-N-H [16] and Li-Mg-Al-N-H [17,18]) were developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to improve the thermodynamic properties of binary Li-N-H system, Li was compositionally substituted by other elements, and several types of ternary or multinary metal-N-H systems (e.g. Li-Mg-N-H [5][6][7][8][9], Li-Ca-N-H [10,11], Li-Al-N-H [12][13][14], Li-B-N-H [12,15], Li-Co-N-H [16] and Li-Mg-Al-N-H [17,18]) were developed.…”
Section: Introductionmentioning
confidence: 99%
“…One is investigating the hydrogen absorption/desorption property [1][2][3][4][5][8][9][10][11][12][13][14][15][16][17][18]; the other is revealing the reaction mechanism involved in the hydrogen absorption/desorption processes [1,6,7,[14][15][16]21]. It was reported that the new ternary imides with mixed alkali and alkaline earth cations, Li 2 Mg(NH) 2 and Li 2 Ca(NH) 2 , were formed along with the dehydrogenation reaction in the Li-Mg-N-H and Li-Ca-N-H systems, respectively [5,8,11,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the physical approaches such as liquefaction and compression, hydrogen storage in the solid state has merits in terms of high volumetric and gravimetric hydrogen contents and, most importantly, safety [1]. Research in many laboratories around the world has focused on the solid-state hydrogen storage materials that are based on three primary approaches: (1) using inorganic solid hydride materials that have reversible dehydrogenation and rehydrogenation characteristics [2][3][4][5][6][7][8][9], (2) using the hydrolysis of alkali-and alkaline-earth metal hydrides and complex hydrides (such as MgH 2 , LiH, LiAlH 4 and LiBH 4 ) [10,11] and (3) using carbon or other adsorbent materials to store hydrogen based on surface adsorption and desorption [12][13][14]. The critical characteristic properties of a solid hydrogen storage material include storage capacity, dehydrogenation temperature, plateau pressure and the reversibility of dehydrogenation and rehydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium aluminum hydride (LiAlH 4 ) has a high hydrogen storage capacity (10.5 wt % H 2 ) and an excellent performance of hydrogen desorption at low temperature; thus, it has received significant attention from researchers. LiAlH 4 decomposes through a two-step process into Al, LiH, and H 2 at T < 250 • C through the intermediate Li 3 AlH 6 , according to reaction scheme (3) [24][25][26][27][28][29].…”
Section: N + H 2 ↔ LI 2 Nh + Lih + H 2 ↔ Linh 2 + 2lihmentioning
confidence: 99%